Will the COVID-19 infection affect the performance of top basketball players? A data-driven analysis - Xiong, Changyue; Wu, Chenxi; Bai, Lu; Yan, Yuxin; Chen, Sumeng (Frontiers in Sports and Active Living, 2024)
Purpose: To investigate the changes in the game performance of high-level basketball players in NBA league before and after the COVID-19 infection.Methods: Athletic statistics were collected from official database for 68 players (19 forwards, 29 guards, 20 centers; mean age 27.14 ± 3.65 years) in the NBA league for 10 games before and after infection with COVID-19. We used a the Kruskal-Wallis analysis of variance to examine the impact caused by COVID-19.Results: Among all 68 players, a statistically significant decrease in plus/minus (Z=-2.392, p=0.017) and free throw shooting (FT% Z=-2.153, p=0.031), occurred compared to the pre-infection with COVID-19. Among the interior players, we found a statistically significant decrease in free throw shooting FT% (Z=2.674, p=0.021), Plus/Minus(Z=-2.371, p=0.018). Among centers and forwards, there was no statistically significant change.The impact of COVID-19 on players' fatigue and cardiorespiratory and muscular endurance may have contributed to the decline in performance, and the impact of detraining due to isolation should not be ignored.